A Change Management for Transformation of Digital Banking In Indonesia - Samosir, Paulima; Jayadi, Riyanto (APIC, 2023)
Bank 4.0 is about the ease of accessing banks or making banks in our hands. Also, the utility whenever and wherever we need financial solutions, in real-time, is programmed according to the behavior of each customer. Banks in their development can choose to change their business model towards digital banking. For this reason, it is necessary to carry out a good change management strategy so that the digital bank transformation process can be carried out. Not only those who are directly involved in the Change Management project but stakeholders within the organization are also involved. This study uses qualitative descriptive methods to design how change management strategies help banks transform into digital banks. The author collects several theories to explore the use of change management in organizations more deeply. In implementing change management, organizations can use a framework as introduced by Kurt Lewin, John Kotter, or the ADKAR framework from PROSCI. The ADKAR model is considered to have advantages in identifying gaps that occur during the change process by instilling awareness, desire, knowledge, ability, and reinforcement. The impact of this transformation led to changes in the organizational structure, business processes, and use of technology within the bank. It is hoped that applying the ADKAR model can help banks change their business models toward digital banking.